Discrepancies in Outcomes by Race and Ethnicity in COVID-19 Patients Receiving Casirivimab and Imdevimab. Issue 1 (January 2023) - Zitek, Tony; Bui, Joseph; Eily, Alyssa; Farcy, David A.
Abstract : The Centers for Disease Control and Prevention has reported that Black and Hispanic individuals are more likely than White individuals to be hospitalized and die from coronavirus disease 2019. To investigate why this may be occurring, we performed a retrospective cohort analysis of patients with coronavirus disease 2019 who received casirivimab/imdevimab, and we compared the outcomes of Black, non-Hispanic patients and Hispanic patients with White, non-Hispanic patients. We found that both Black, non-Hispanic patients and Hispanic patients are more likely to make a return visit to the emergency department within 28 days after treatment as compared with White, non-Hispanic patients. These findings remained true even after adjusting for differences in vaccinations rates, and thus they suggest that access to vaccination and treatment do not fully explain the racial and ethnic disparities in outcomes. Abstract : Objectives: The Centers for Disease Control and Prevention has reported increased rates of coronavirus disease 2019 (COVID-19)–related hospitalizations and deaths in Black and Hispanic individuals. One contributing factor to this may be a difference in access to treatment. We thus sought to compare the outcomes of Black, non-Hispanic patients and Hispanic patients with White, non-Hispanic individuals using a group of patients with COVID-19 who received casirivimab/imdevimab. Methods: This was a secondary analysis of data from a previously published retrospective chart review of patients who received casirivimab/imdevimab for COVID-19 between December 9, 2020 and August 20, 2021, when they were treated at one of three facilities within a single hospital system. We compared the baseline characteristics (including age, sex, body mass index, duration of symptoms, and vaccination status) and outcomes of Black, non-Hispanic patients and Hispanic patients with those of White, non-Hispanic patients. Our primary outcome was the odds of a return visit to the emergency department (ED) within 28 days of treatment as assessed by multivariate logistic regression. We also assessed the rates of return visits to the ED for symptoms caused by COVID-19, hospitalizations, and hospitalizations from hypoxia. Results: In total, 1318 patients received casirivimab/imdevimab for COVID-19 at the three study facilities. Of these, 410 (31.1%) identified themselves as White and non-Hispanic, 88 (6.7%) as Black and non-Hispanic, and 736 (55.8%) as Hispanic. Vaccination rates at the time of treatment were as follows: Black, non-Hispanic 10.2%, Hispanic 13.6%, and White, non-Hispanic 21.5%. On multivariate analysis, the odds of return visits to the ED within 28 days were higher for Black, non-Hispanic patients and Hispanic patients as compared with White, non-Hispanic patients, with odds ratios of 2.8 (95% confidence interval [CI] 1.4–5.5, P = 0.003) and of 2.3 (95% CI 1.5–3.6, P = 0.0002), respectively. For hospitalizations caused by hypoxia within 28 days of treatment, the adjusted odds ratio for Black, non-Hispanic patients was 3.4 (95% CI 1.1–10.5, P = 0.03) as compared with White, non-Hispanic patients. There were no other statistically significant differences among groups in regard to subsequent hospitalizations within 28 days. Conclusions: Black, non-Hispanic patients and Hispanic patients are more likely to make a return visit to the ED within 28 days after casirivimab/imdevimab treatment for COVID-19 as compared with White, non-Hispanic patients. This holds true even when adjusting for higher vaccination rates among White, non-Hispanic individuals.